2021
DOI: 10.1371/journal.pone.0249149
|View full text |Cite|
|
Sign up to set email alerts
|

Improved sensitivity, safety, and rapidity of COVID-19 tests by replacing viral storage solution with lysis buffer

Abstract: Conducting numerous, rapid, and reliable PCR tests for SARS-CoV-2 is essential for our ability to monitor and control the current COVID-19 pandemic. Here, we tested the sensitivity and efficiency of SARS-CoV-2 detection in clinical samples collected directly into a mix of lysis buffer and RNA preservative, thus inactivating the virus immediately after sampling. We tested 79 COVID-19 patients and 20 healthy controls. We collected two samples (nasopharyngeal swabs) from each participant: one swab was inserted in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Previous studies on SARS-CoV-2 revealed that the Ct values were increased by time at different storage temperatures ( Erster et al, 2021 ; Kim et al, 2021 ; Engelmann et al, 2021 ). Although it was not statistically significant, in our study this was the case for human RNase P gene Ct values; on contrary the Ct values for viral genes ORF and N showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on SARS-CoV-2 revealed that the Ct values were increased by time at different storage temperatures ( Erster et al, 2021 ; Kim et al, 2021 ; Engelmann et al, 2021 ). Although it was not statistically significant, in our study this was the case for human RNase P gene Ct values; on contrary the Ct values for viral genes ORF and N showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 95%
“…In all 24 cases where more than one positive individual was part of the pool, the pool tested positive. preservative), as previous works showed an advantage in sensitivity to lysis buffer over VTM [15]. This higher sensitivity of the pool may result from the accumulation effect of viral RNA from several positive samples in the pool, each having a viral load that was below detection level when tested individually, but rendering the pool positive.…”
Section: Comparison Between Ct Values Of Swab-pools and Individual Te...mentioning
confidence: 96%
“…Simple and fast detection methods are available, but the gold standard is still qRT-PCR of nasal or nasopharyngeal swabs, which typically takes several hours and is carried out in an authorized laboratory [7,8]. Several approaches were developed to increase the throughput of qRT-PCR testing, e.g., sample pooling, which enables a shorter turnaround time with a slight reduction in test sensitivity [9][10][11][12][13][14], as well as using lysis buffer for swab collection instead of viral preservation medium [15]. While numerous studies were published on sample pooling [e.g., [9][10][11][12][13]], only a few studies were published on swab-pooling [16][17][18][19][20], with only one large-scale study [21].…”
Section: Introductionmentioning
confidence: 99%
“…We expect the uncertainty associated with sampling by oro- and nasopharyngeal swab probing to be reduced when including saliva, as in our preferred procedure. The uncertainty may be reduced further with improvements over standard swabs [ 28 ] or extraction buffer composition, as discussed for tests detecting nucleic acids [ 29 ]. We note that our procedure deviates from that recommended by Abbott and that a clinical study is planned to obtain more robust data from outbreaks of COVID-19.…”
Section: Discussionmentioning
confidence: 99%